2021
DOI: 10.1016/j.cca.2021.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and Mid-Regional proAdrenomedullin: What role in SARS-CoV-2 infected Patients?

Abstract: Background Endothelial dysfunction, a major complication of SARS-CoV-2 infectionplaying a key-role in multi-organ damage, carries high risk of mortality. Aim To investigate the potential role of Mid-Regional pro-Adrenomedullin (MR-proADM) in detecting endothelial damage with a view to stratifying the risk of adverse events (length of stay, death, admission in Intensive Care Unit) and/or disease resolution. Materials and Methods In 135 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…To our knowledge, this is the largest study evaluating the role of MR-proADM in critically ill COVID-19 patients. Other studies have evaluated the role of MR-proADM in the setting of COVID-19 pandemic [22][23][24][25][26][27][28][29][30]. Benedetti et al [22] evaluated MR-proADM and other biomarkers in 21 ICU patients (measured on the 1st, 2nd, 3rd, and 5th day of admission) to determine their predictive value for mortality; the optimal cut-off for MR-proADM was 1.07 nmol/L (sensitivity of 91% and specificity of 71%; p = 0.006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the largest study evaluating the role of MR-proADM in critically ill COVID-19 patients. Other studies have evaluated the role of MR-proADM in the setting of COVID-19 pandemic [22][23][24][25][26][27][28][29][30]. Benedetti et al [22] evaluated MR-proADM and other biomarkers in 21 ICU patients (measured on the 1st, 2nd, 3rd, and 5th day of admission) to determine their predictive value for mortality; the optimal cut-off for MR-proADM was 1.07 nmol/L (sensitivity of 91% and specificity of 71%; p = 0.006).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal cut-off point for predicting mortality was 0.93 nmol/L. Zaninotto et al [29] retrospectively evaluated the potential role of MR-proADM in detecting endothelial dysfunction and its usefulness for stratifying COVID-19 patients; with a median time elapsed from the hospital admission to MR-proADM measurement of 7 days. A total of 135 patients were included, and the findings suggested that higher MR-proADM levels are associated with a greater risk for adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…MR-proADM, an AM synthesis marker, has been recognized as the best marker for sensitivity and specificity in sepsis endothelial dysfunction [101]. A significant MR-proADM increase has been reported in patients with COVID-19, especially in severe conditions, such as acute respiratory distress syndrome (ARDS) [26][27][28][29][30][31][32][33][34][35][36]. More importantly, increased MR-proADM is the best predictor of mortality in patients with COVID-19; the area under the receiver operating characteristic curve (ROC AUC) was distributed in a high range (0.78-0.951) [27][28][29][31][32][33][34][35].…”
Section: Am and Covid-19mentioning
confidence: 99%
“…A significant MR-proADM increase has been reported in patients with COVID-19, especially in severe conditions, such as acute respiratory distress syndrome (ARDS) [26][27][28][29][30][31][32][33][34][35][36]. More importantly, increased MR-proADM is the best predictor of mortality in patients with COVID-19; the area under the receiver operating characteristic curve (ROC AUC) was distributed in a high range (0.78-0.951) [27][28][29][31][32][33][34][35]. MR-proADM plasma concentrations in COVID-19 survivors did not increase after hospital admission; however, concentrations increased significantly in non-survivors [35].…”
Section: Am and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation